Nitrogen Accumulation in Forests. Exposure Monitoring by Mosses. (2007) - Pesch, Roland; Schröder, Winfried; Schmidt, Gunther
Abstract : At present, there is still little information on nitrogen (N) accumulation in forests contrasting with the crucial importance of N in forest ecosystems. This work analyzes the N bioaccumulation in mosses from forested areas from Lower Saxony and North Rhine-Westphalia (two of 16 federal states of Germany), the Weser Ems Region (part of Lower Saxony), and the Euro Region Nissa (covering the Czech Republic, Germany, Poland). The studies involved samples collected from 190 sites between 1998 and 2005. Different spatial scales and regional differences in land use were chosen to assess the factors affecting N bioaccumulation in forested areas. A continuous reduction of N bioaccumulation was found from Lower Saxony (a region where agriculture is most predominant) to North Rhine-Westphalia (mostly urban). The Weser Ems Region (an agricultural region) showed a higher N concentration in mosses than the Euroregion Nissa (a former industrial region). Statistical analyses performed at the different spatial scales revealed that the areas showing greater agricultural and livestock spatial densities favor N bioaccumulation in mosses. N concentration in mosses was moderately correlated with the N concentration in the leaves and needles of the surrounding trees. No significant relationships were found regarding the crown density of forest trees or N deposition estimations from a combination of atmospheric models and deposition measurements.